Coleta e gestão eficiente de dados agropecuários em uma arquitetura serverless de big data - Ferreira, Wellington de Souza (2025)
With the growing need to manage large volumes of data, the use of Big Data architectures has become essential. An effective, simple, and cost-efficient approach for implementing this type of architecture is through serverless techniques. This paper details a serverless architecture for data collection and management, utilizing Amazon Web Services (AWS) technologies and services. To develop the architecture, agricultural data from the state of Paraná was collected. The proposed architecture was implemented and tested, and the results obtained demonstrate its effectiveness and feasibility in various use cases. Tests were conducted to evaluate the execution time and cost of the architecture, confirming that it offers low costs and meets the objectives set forth in this paper.